Pediatric vascular anomalies in Austria. Where are we at? A survey among primary care pediatricians - Gasparella, Paolo; Senica, Simone O.; Singer, Georg; Banfi, Chiara; Flucher, Christina; Beqo, Besiana P.; Till, Holger; Haxhija, Emir Q. (Frontiers in Pediatrics, 2023)
Introduction: Vascular anomalies (VAs) are rare conditions and affected patients often experience a difficult patient journey. Timely diagnosis is only possible if primary caregivers are aware of the anomalies and are connected with dedicated specialists. Aim of our survey was to investigate the knowledge about diagnostic and therapeutic possibilities for children with VAs, and the existing networking among primary pediatric caregivers in Austria. Methods: Primary care pediatricians in Austria were invited to complete an online questionnaire consisting of 28 questions focusing on pediatric VAs. Results: Out of 373 invited pediatricians 93 (25%) returned the questionnaires, 86 of which were complete. Most physicians (39/93 42%) answered that they see between 15 and 30 patients with infantile hemangiomas per year. Vascular malformations are rarely treated in the primary care setting; most primary care pediatricians (58/86, 67%) reported that they currently treat fewer than 5 patients with such type of VAs. There was unequivocal agreement among the participants (84/86, 98%) on the need to establish a network of specialists and a registry dedicated to pediatric VAs. Conclusions: This survey represents the first study shedding light on the awareness of VAs among Austrian pediatricians and can serve as a basis for future investigations and advances in the management of these conditions in Austria and other countries with a similar healthcare setting.